Flowering of Two Cultivras of Durian (Durio zibethinus Rumph. ex Murray) Treated by Paclobutrazol - ., Sakhidin; ., Darjanto; Rohadi Suparto, S (KnE Life Sciences, 2019)
The research aimed to know the effect of application time of paclobutrazol on flowering of two cultivars of durian (Durio zibethinus Rumph. ex Murray). Experiement was conducted in Pageralang village, Kemranjen district, Banyumas regency Central Java, Indonesia by using durian tree of 10 y.o. The treatments were application time of paclobutrazol ( June, July, and August) and cultivars (Kani, Monthong). Each treatment was replicated four times, so there were 24 trees of durian. Observed variables were time of flowering, percentage of flowery branch, total number of flower, number of flower panicle, number of young fruits, and fruitset. The results of research showed that application of paclobutrazol in August induced flowering faster than application in June and July. Application of paclobutrazol induced flowering of Kani faster than Monthong. Kani has higher total number of flower, number of flower panicle, and number of young fruits. The effect of application time of paclobutrazol on flowering of durian was not effected by varieties. Keywords: Application time, Cultivar, Durian, Flowering, Paclobutrazol